2017
DOI: 10.1021/acs.iecr.7b02125
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Shortcut Design Method of Divided Wall Columns Exemplified by a Liquefied Petroleum Gas Process

Abstract: Designing a sustainable and economical distillation system is a big global challenge in the industrial chemical field. To address this issue, one of most promising solutions is the so-called dividing wall columns addressed in this work, which not only can cut energy cost but also use limited installation space. An improved shortcut design approach is developed in this work to provide accurate models for each section of dividing wall columns; meanwhile Underwood’s and Gilliland’s equations are employed to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Since constructing such diagrams requires the design of each alternative at numerous different values of the feed composition and other variables, most engineers have used shortcut design methods such as assuming constant relative volatility and constant molar overflow and using the vapor rate or total energy consumption as an objective function. Furthermore, when comparing alternatives to the conventional direct and indirect sequences, most authors reported that DWCs provide cost savings. However, most do not considered the possibility of stacking the two conventional columns, i.e., adjusting the column pressures so that direct heat transfer between the condenser of one column and the reboiler of the other column is possible. …”
Section: Introductionmentioning
confidence: 99%
“…Since constructing such diagrams requires the design of each alternative at numerous different values of the feed composition and other variables, most engineers have used shortcut design methods such as assuming constant relative volatility and constant molar overflow and using the vapor rate or total energy consumption as an objective function. Furthermore, when comparing alternatives to the conventional direct and indirect sequences, most authors reported that DWCs provide cost savings. However, most do not considered the possibility of stacking the two conventional columns, i.e., adjusting the column pressures so that direct heat transfer between the condenser of one column and the reboiler of the other column is possible. …”
Section: Introductionmentioning
confidence: 99%
“… , However, conventional ED has a relatively low thermodynamic efficiency, and the high quality energy input is required in the reboiler to perform the separation task. , Furthermore, the increasing awareness of the energy crisis has made process intensification a promising trend for energy savings strategies in chemical engineering. Therefore, a separation technology, called “dividing-wall columns or DWCs”, separation configuration was proposed and could be applied in the separation of multicomponent or nonideal azeotrope mixtures and have significant advantages than conventional distillation. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a separation technology, called "dividing-wall columns or DWCs", separation configuration was proposed and could be applied in the separation of multicomponent or nonideal azeotrope mixtures and have significant advantages than conventional distillation. [10][11][12][13]29,30 The divided-wall at the top of the DWC configuration divides the column into two rectifying sections and a shared stripping section, and the dividing-wall is often implemented in the extractive separation denoted as extractive dividing-wall column (EDWC) for separating an azeotropic mixture (see Figure 2a). 14−20 A thermodynamically equivalent process of the EDWC in Aspen Plus is demonstrated in Figure 2b.…”
Section: Introductionmentioning
confidence: 99%
“…It could separate three or four pure fractions in a single shell . The short‐cut and rigorous simulation , optimization , control , and implementation have been well studied. In a standard arrangement of a three‐product DWC, the light component and the heavy component have a direct increasing or decreasing trend in the prefractionator and the main column.…”
Section: Introductionmentioning
confidence: 99%